3-(2-Hydroxyethyl)-1-(4-nitrophenyl)-1H-imidazol-3-ium bromide - Halliru Ibrahim; Sizwe J. Zamisa; Muhammad D. Bala; Pinkie Ntola; Holger B. Friedrich (IUCrData)
The molecular structure of the title salt, C11H12N3O3+·Br−, reveals near co-planarity between the the imidazole and 4-nitrobenzene moieties with a dihedral angle of 8.99 (14)° between their planes. A prominent feature in the molecular packing is the bromide anion acting as a double acceptor for O—H...Br and C—H...Br hydrogen-bonds, leading to a linear chain propagating along [110]. The crystal studied was refined as an inversion twin, with the minor component = 0.081 (8).